The Business Plan How to Win Your Investors$1 (BConfidence /s - Schwetje, Gerald; Vaseghi, Sam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This book provides the essentials to write a successful businessplan. The represented methods and best practices have been approved over many years in practice with many management consulting engagements. The book is easily structured, it has a pragmatic emphasis and an autodidactic approach. The reader gets acquainted with the skills and competencies as well as tools, required for the planning and development of the businessplan project. This way of approach gives even those readers, with less background in business, a professional and excellent introduction to the field of business planning. Each section of the book closes with a set of crucial key questions, in the manner of a quick due diligence, these results essentially give a roadmap, independent of the industries applied. The book allows the reader to make up a clear and transparent portrait about his/her company respectively entrepreneurial intention. By this way, the reader is able to estimate himself/herself the real risks and chances.
Necessity of planning -- Business plan project -- Executive summary -- Business idea and strategic goals -- Management team and organization -- Products and services -- Market and competition -- Marketing and sales -- Research and development -- Production -- Procurement and logistics -- Finance -- The way to the investor.
Keywords: Business; Entrepreneurship; New business enterprises; Organization; Planning; Business and Management; Start-Ups/Venture Capital; Entrepreneurship; Organization; Electronic books